Factors Affecting the Capital Structure of BSE-100 Indian Firms: A Panel Data Analysis - Khare, Sumi; Rizvi, Saima (Indian Journal of Finance, 2011)
Purpose: The purpose of the study is to examine important variables that impact debt-equity choice of BSE-100 index companies. Moreover, on the basis of signs of the coefficients, the paper examines the applicability of trade-off or pecking order theories for BSE-100 index companies. Methodology: Financial data was collected over 10 years from year 2000 to 2009 for BSE listed firms using Prowess source. A Panel data analysis was used for cross-sectional time series data. Leverage defined as ratio total liabilities to total asset is taken as dependent variable. Findings: The results showed returns on assets to be most significant factor for leverage followed by profit margin on sales and DO (ratio of total depreciation to total assets).Also, pecking order theory was found to be applicable for capital structure of BSE index listed companies. Research limitations: Data for some companies is not available through prowess. Practical Implication: Capital structure is important for companies to understand how much debt they need to employ. Therefore, this study will aid companies arrive at an optimal level of debt in their capital structure. Social Implication: Some of the big investment banks failed in United States because of high level of leverage employed by them and as a result of which, investors suffered losses. Therefore, it is essential for companies to arrive at the optimal debt equity ratio. Originality/Value: The main value of this study is the identification of the factors that influence the capital structure of BSE listed firms in India.